Toll-Like Receptor Activation and B Cell Maturation Via MyD88-Dependent Pathway Under Hyperglycemia Condition - Riandini Aisyah; Safari Wahyu Jatmiko (Universitas Muhammadiyah Surakarta, 2024)
hyperglycemia causes a degenerative syndrome that involves an inflammatory process with an increase in certain proinflammatory cytokines and chemokines which in the process will activate B cells to produce immunoglobulins through several mechanisms. One of the interesting mechanisms is the mechanism via the MyD88 pathway. Objectives: to explore the role of MyD88 adapter protein in Toll-like receptor activation and B cell maturation under hyperglycemia conditions. Methods: a literature review was done to answer the study objectives. Results: Class switching process under hyperglycemia conditions involves activation of NFkB through the inflammatory MyD88-dependent pathway to trigger the expression of TLR and B cell maturation and proliferation as well as antibody production. The MyD88 adapter protein is a protein formed by stimulation of pro-inflammatory cytokines IL-6 and plays a role in the continuation of signals from the TLR and IL-1 pathways. Mature B cell stimulation induces 2 genetic changes in the Ig gene locus, called somatic hypermutation (SHM) and class switch recombination (CSR) to produce antibodies. Changes in immunoglobulin genes occur related to changes in certain DNA segments at the locus of genes where CSR occurs, this gene change requires the role of AID (activated-induced cytidine deaminase) in DNA cleavage. AID in mature B cells is activated by proinflammatory cytokines via induction of NfKB activation via the inflammatory MyD88-dependent pathway. Conclusion: Toll-like receptor activation plays a crucial role in B cell maturation activated by pro-inflammatory cytokine via MyD88 dependent-NFkB activation.